Determinants and prognostic relevance of aortic stiffness in patients with recent ST-elevation myocardial infarction. (14th October 2021) - Lechner, I; Reindl, M; Tiller, C; Holzknecht, M; Mayr, A; Klug, G; Brenner, C; Bauer, A; Reinstadler, S J; Metzler, B
Abstract: Background: The association between aortic stiffness, cardiovascular risk factors and prognosis in patients with recent ST-elevation myocardial infarction (STEMI) is poorly understood. We analyzed the relationship between cardiovascular risk factors and arterial stiffening and assessed its prognostic significance in patients with recent STEMI. Methods: We prospectively enrolled 408 consecutive patients who sustained a first STEMI and underwent primary percutaneous coronary intervention (PPCI). Aortic pulse wave velocity (PWV), a direct measure of aortic stiffness, was determined by the transit-time method using velocity-encoded, phase-contrast cardiac magnetic resonance imaging. Patient characteristics were acquired at baseline and major adverse cardiac and cerebrovascular events (MACCE) were assessed at 13 (interquartile range [IQR] 12–31) months. Cox regressionand logistic regression analysis were performed to explore predictors of PWV and MACCE. Results: Median aortic PWV was 6.6 m/s (IQR 5.6–8.3m/s). In multivariable analysis, age (odds ratio [OR] 1.10, 95% confidence interval [CI], 1.08–1.14, p<0.001) and hypertension (OR 2.45, 95% CI, 1.53–3.91, p<0.001) were independently associated with increased PWV. Sex, diabetes, smoking status, dyslipidemia, and obesity were not significantly associated with PWV in adjusted analysis (all p>0.05). High PWV significantly and independently predicted occurrence of MACCE in adjusted analysis (hazard ratio [HR] 2.45, 95% CI 1.19–5.04, p=0.014). Conclusion: In patients with recent STEMI, the impact of classical cardiovascular risk factors on aortic stiffness is mainly dependent on age and increased blood pressure. Increased aortic stiffness is associated with adverse clinical outcome post-STEMI, suggesting it as a relevant therapeutic target in this population. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Austrian Science Fund (FWF)Austrian Society of Cardiology